Necessary work design characteristics for younger workers’ attitudes and behaviors - Dello Russo, S.; Mirfakhar, A. S.; Zaniboni, S.; Antino, M. (Academy of Management Annual Meeting Proceedings, 2022, 2022)
Managing younger workers in organizations requires motivating them to engage in positive attitudes and behaviors and refrain from negative ones. Based on needs and motives theories, work design characteristics can act as motivational factors with younger workers. Exploring which of the work characteristics are necessary, as opposed to sufficient, to achieve desired levels of younger workers’ positive and negative attitudes and behaviors, is of great importance for organizations considering their limited resources. Taking the Necessary Condition Analysis approach (necessary conditions are those whose absence guarantees the absence of the outcome) and collecting a sample of 165 employees under 40, five work design characteristics (i.e., autonomy, task significance, interdependence, peer support and supervisor support) were analyzed as possible necessary conditions for enabling daily positive (i.e., work engagement, crafting) and constraining daily negative (i.e., cynicism, and incivility) attitudes and behaviors. Based on our findings, task significance, supervisor and peer support are necessary conditions for work engagement among younger workers. To enable crafting among them, autonomy and supervisor support are necessary. Not only work design characteristics do not constrain negative outcomes, but interdependence (either received or initiated) even enables cynicism and incivility (for which also task significance is an enabler). This study contributes by conceptualizing work design characteristics as necessary motivational factors and empirically testing them using necessary condition analysis.